Assessment and Management of Level Crossing Risks - Iva Zitnikova; Lenka Malerova; Rene Pribyl; Michal Schwarz; Ales Bernatik; Lenka Kopecka (Communications - Scientific letters of the University of Zilina, 2011)
The goal of the project “Assessment and Management of Level Crossing Risks” was to make a comprehensive analysis of safety of level crossings in the Moravian-Silesian Region. The project is divided into several phases including technical and legislative aspects as well as issues of human factor affecting the occurrence of incidents related to level crossings. In individual chapters, results of questionnaire survey concerning the given problems are processed, the analysis of level crossing risks is made and measures to reduce the risks associated with level crossing traffic are proposed.